IMPLEMENTASI MODEL PEMBELAJARAN DHARMAGITA DALAM MENINGKATKAN KREATIVITAS MAHASISWA - Wiasti, Ni Komang; Wirata, I Wayan (Padma Sari: Jurnal Ilmu Pendidikan, 2025)
This study aimed to analyze the implementation of various Dharmagita-based learning models at IAHN Gde Pudja Mataram. Dharmagita learning played a strategic role in transmitting cultural and spiritual-religious values, thus requiring a contextual, participatory, and meaningful pedagogical approach. A qualitative method was used, with data collected through observation, in-depth interviews, and documentation. Data analysis employed an interactive model consisting of four main stages: data collection, data condensation, data display, and conclusion drawing or verification. The findings revealed that the implementation of the Contextual Learning Model Based on Dharmagita, the Cooperative Learning Model Based on Dharmagita, the Project-Based Learning Model Based on Dharmagita, and the Audio-Visual Learning Model Based on Dharmagita successfully created an active, engaging, and relevant learning atmosphere for students. These models brought diverse approaches to instilling ethical and spiritual values, while encouraging students to develop their personal potential in the field of Dharmagita. The learning process led to increased student creativity, as evidenced by participation in extracurricular activities such as student organizations and competitions related to Dharmagita. The lecturer’s role as a facilitator also proved essential in ensuring quality learning, which was reflected in student achievements at both local and national levels. The findings highlight the importance of pedagogical innovation in preserving dharma values among the younger generation through the development of innovative learning models grounded in Hindu religious values